Moral Communities and Institutional Misconduct: A Reassessment of Religious Contextual Influences on Inmate Behavior - Drakeford, Leah (Crime & delinquency, 2020)
Most of the research into religious influences on inmate misconduct has been undertaken with respect to personal religious participation. However, the religious environment of prisons offers potential influences on inmate behavior by providing social control and support. Currently, the literature is mixed regarding the association between religious context and inmate behavior. This article reconciles the divergent findings regarding religious contexts, and integrates recently emergent directions in religious contextual research. Using nationally representative data of inmates in state and federal prisons, I estimate multilevel models of several different forms of misconduct. The results indicate a relationship between religious context and each form of misconduct, highlighting the role of cultural contexts on inmate behavior.